Detection of beta lactamase in sputum. Issue 8 (August 1994) - Connell, C; Aspinall, S; Corkill, J
Abstract : AIMS--To develop a rapid, sensitive, and reproducible test for the detection of beta lactamase in sputum, and to relate these findings to bacteriological culture results. METHODS--One hundred and twenty sputum samples from inpatients were investigated for beta lactamase activity using the chromogenic cephalosporin nitrocefin. Sputum samples were sonicated and incubated aerobically at 37 degrees C with nitrocefin for up to two hours. Positive results (production of a red colour) were treated with blue sepharose beads to remove albumin (which can cause non-specific hydrolysis of nitrocefin) and retested. Samples were also cultured for both aerobic and anaerobic bacteria, with all isolates being tested for beta lactamase production using nitrocefin. All positive sputum samples and beta lactamase producing isolates were further examined by isoelectric focusing (IEF) to determine isoelectric point(s) (pIs). RESULTS--The process of sonication and albumin removal had no demonstrable effect on beta lactamase activity. Forty seven of the 120 sputum samples were positive on initial testing, and of these, 16 remained positive following removal of albumin. These 16 subsequently yielded 19 beta lactamase producing bacteria. All sputum samples yielding beta lactamase producing bacteria were also positive on direct nitrocefin testing. On no occasion were sputum samples positive in the absence of enzyme producing bacteria--that is, the test was both 100% specific and 100% sensitive. The presence of beta lactamase activity in the sputum samples was also confirmed using a microbiological method. In 11 sputum samples the beta lactamases detected had similar pI values to the beta lactamases obtained from their bacterial isolates. CONCLUSION--Detection of beta lactamase activity in sputum using nitrocefin, after treatment with blue sepharose beads, is a rapid, reproducible test with high specificity and sensitivity. Analytical isoelectric focusing showed that for 11 of the 16 positive sputa, the source of the beta lactamases could be traced to their concurrent bacterial isolates.